Updatable dataset revealing decade changes in land cover types in Mongolia. (14th February 2022) - Wang, Juanle; Wei, Haishuo; Cheng, Kai; Ochir, Altansukh; Shao, Yating; Yao, Jinyi; Wu, Yuxin; Han, Xuehua; Davaasuren, Davaadorj; Chonokhuu, Sonomdagva; Zhou, Yezhi; Zhang, Min; et al.
Abstract: The Mongolian Plateau (MP) is in the interior of Northeast Asia, far from the sea, and is extremely vulnerable to climate change and the deleterious effects of human activity. The United Nations Sustainable Development Goals (SDGs) explicitly set land degradation neutrality (LDN) as one of the sub‐goals of the seventeen main tasks. However, achieving this goal in Mongolia, a country with a fragile and sensitive ecological environment and a lack of high‐precision land cover and land degradation monitoring data, is challenging. In this study, we established rules for remote sensing‐based land cover classification and reference threshold ranges based on an object‐oriented remote sensing interpretation method. Then, we obtained the refined land cover data of Mongolia from 1990, 2000, 2010 and 2020 with 30‐m resolution. The land cover classification of Mongolia comprises 11 categories: forest, meadow steppe, real steppe, desert steppe, barren, sand, desert, ice, water, cropland and built area. The overall classification accuracies, corresponding to the aforementioned data year, were 82.26%, 82.77%, 92.34% and 81.84%, respectively. We found that the land cover showed an apparent law of zonal gradual change. Among them, barren land, real steppe, desert steppe and forest were consistently the four major land cover types. Since the last 30 years, barren land areas present an overall decreasing trend, showing a trend of shrinking to the south. Overall, real steppe presents a wavelike decreasing trend, and desert steppe shows a fluctuating increasing trend. The forest area is relatively stable with no notable changes in spatial distribution. The dataset of this study fills the gaps in high‐resolution land cover data for Mongolia, and it can provide fundamental scientific data to support sustainable development in the MP. Abstract : Land cover distribution map of Mongolia in 2020.